Proceedings of the 2016 CHI Conference Extended Abstracts on Human Factors in Computing Systems 2016
DOI: 10.1145/2851581.2892461
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Interactive Lighting for Fashion Store Windows

Abstract: Smart light technology offers new dynamic and interactive capabilities that extend the potential of traditional lighting systems of attracting people and affecting their mood, emotions, and behavior. Our research explores smart lights in the context of shopping windows. The paper describes an extensive empirical study that has been performed for 5 weeks in a fashion store located a top-level shopping area in Milan (Italy). The data automatically collected from over 1 million people passing by or stopping in fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…More specifically, according to Pantano E, et al [50], innovative interactive technologies increase consumer willingness to enter a store and create positive wordof-mouth. Cremonesi, et al [51] have explored the effect of smart light technology in storefront windows on shopper experiences in comparing three different light configurations: static, dynamic, and interactive. They have found that interactive smart lights raise store attractiveness and shopper engagement as well as enhance shopping experiences.…”
Section: Smart Storefront Windowsmentioning
confidence: 99%
“…More specifically, according to Pantano E, et al [50], innovative interactive technologies increase consumer willingness to enter a store and create positive wordof-mouth. Cremonesi, et al [51] have explored the effect of smart light technology in storefront windows on shopper experiences in comparing three different light configurations: static, dynamic, and interactive. They have found that interactive smart lights raise store attractiveness and shopper engagement as well as enhance shopping experiences.…”
Section: Smart Storefront Windowsmentioning
confidence: 99%
“…More specifically, according to Pantano E, et al [50], innovative interactive technologies increase consumer willingness to enter a store and create positive wordof-mouth. Cremonesi, et al [51] have explored the effect of smart light technology in storefront windows on shopper experiences in comparing three different light configurations: static, dynamic, and interactive. They have found that interactive smart lights raise store attractiveness and shopper engagement as well as enhance shopping experiences.…”
Section: Smart Storefront Windowsmentioning
confidence: 99%
“…In the broader context of HCI research, prior work has examined several application areas in fashion using technology, such as in-store environments [7], while other researchers have focused on the relationships between fashion and clothing [15], understanding the design of electronics with fashion lenses [14] and design principles from fashion itself [24]. Pan and Stolterman described scenarios for HCI driven by fashion from different perspectives, such external fashion concepts influencing the field, as well as fashion concepts that go in and out of fashion within the field itself [25].…”
Section: Fashion and Technologymentioning
confidence: 99%